Unveiling the Antibacterial Potential of Arumanis Mango (Mangifera indica L.) Leaf Extract Against Enterococcus faecalis: A Comparative Study with Melinjo (Gnetum gnemon L.) - Lokanata, Shieny; Roselyn Avrillia; Marco Luman; Yossye Joyce Magdalena Br Sirait; Daffa Nabilah Panggabean (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Root canal infections, frequently caused by the bacterium Enterococcus faecalis due to its resistance to conventional treatments, present a significant challenge in dental practice. Effective disinfection of the root canal system is crucial for successful endodontic therapy, necessitating the exploration of alternative irrigating solutions. This study aimed to evaluate and compare the in vitro antibacterial efficacy of Arumanis mango (Mangifera indica L.) leaf extract and melinjo (Gnetum gnemon L.) leaf extract against Enterococcus faecalis. Methods: This in vitro experimental study employed the disc diffusion method to assess the antibacterial activity of ethanolic extracts of Arumanis mango and melinjo leaves against Enterococcus faecalis. The extracts were tested at three different concentrations: 25%, 50%, and 75%. Chlorhexidine 0.2% and distilled water served as positive and negative controls, respectively. The diameter of the inhibition zones around the discs was measured after incubation. Phytochemical screening of both extracts was also conducted. Results: The phytochemical screening revealed the presence of flavonoids, alkaloids, and tannins in both Arumanis mango and melinjo leaf extracts. However, the antibacterial activity varied significantly. Melinjo leaf extract did not exhibit any measurable inhibitory effect on Enterococcus faecalis at any of the tested concentrations. In contrast, Arumanis mango leaf extract demonstrated significant antibacterial activity at concentrations of 50% and 75%, with mean inhibition zone diameters of 11.73 ± 0.75 mm and 12.90 ± 0.30 mm, respectively. Statistical analysis using the Kruskal-Wallis test and post-hoc Mann-Whitney U test confirmed a significant difference in the antibacterial activity between the Arumanis mango leaf extract at 50% and 75% concentrations and the melinjo leaf extract at all tested concentrations, as well as the distilled water control. The positive control, chlorhexidine 0.2%, showed the largest inhibition zone (15.10 ± 0.10 mm). Conclusion: The findings of this study indicate that the ethanolic extract of Arumanis mango (Mangifera indica L.) leaves possesses significant in vitro antibacterial activity against Enterococcus faecalis, suggesting its potential as a natural alternative irrigating solution in endodontic treatment. Conversely, under the conditions of this study, melinjo (Gnetum gnemon L.) leaf extract did not demonstrate any antibacterial effect against this specific bacterium. Further research is warranted to explore the clinical efficacy and safety of Arumanis mango leaf extract in root canal disinfection.